2019
DOI: 10.2151/jmsj.2019-001
|View full text |Cite
|
Sign up to set email alerts
|

A Statistical Study of Wind Gusts in Japan Using Surface Observations

Abstract: In this study, the characteristics of wind gusts in Japan in the period from 2002 to 2017 were examined using surface meteorological data recorded at 151 weather observatories throughout Japan. This study does not focus on particular phenomena, such as tornadoes and downbursts, which cause wind gusts. A wind gust is defined on the basis of the gust factor and the amount of increase and decrease of the 3s mean wind speed from the 10min mean wind speed. A total of 3,531 events were detected as wind gusts. The fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…10a). This finding is consistent with reports from previous studies that the strongest gusts frequently occurred in the northeastern quadrant [48,49] . Note that the smaller number of observations in the SW quadrant partly contributes to its weaker estimated speed since insufficient data representativeness undermines the possibility of capturing extremes.…”
Section: Wind Gust Parameters In Four Quadrantssupporting
confidence: 94%
“…10a). This finding is consistent with reports from previous studies that the strongest gusts frequently occurred in the northeastern quadrant [48,49] . Note that the smaller number of observations in the SW quadrant partly contributes to its weaker estimated speed since insufficient data representativeness undermines the possibility of capturing extremes.…”
Section: Wind Gust Parameters In Four Quadrantssupporting
confidence: 94%
“…Using a high‐resolution numerical simulation, Miyamoto et al (2022) showed that the warm sea‐surface temperature extending into the near‐coastal areas and the weak vertical wind shear contributed to Faxai 's compact and axisymmetric inner core structure at landfall. Mashiko (2020) studied the spatiotemporal characteristics of Faxai 's strong winds and gusts during landfall and compared them with strong wind events in the Kanto region during other typhoons that had passed near Tokyo Bay after 1994. He found that only Typhoon Danas (2001) had an axisymmetric inner core structure typical of mature TCs as seen in Faxai (2019).…”
Section: Introductionmentioning
confidence: 99%